Communicating culture through magical realism perspectives on selected Malaysian short stories - Mas Rynna Wati Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2016)
Malaysia is a multicultural society with diverse cultures, races and religions. Hence, the government had to set up policies to enhance mutual understanding for the betterment of the nation. This would include the setting up of policies on national language and literature to strengthen the harmony among races. It was then that the Malay literary movement or known as ASAS 50 introduced its philosophy, Seni untuk Masyarakat, or art for the masses, was somehow deemed right to support the national agendas after the independence. However, after more than 50 years of achieving independence and national stability, the nation had witnessed the emergence of young writers who adamantly in wanting for their works to be uniquely known; sets them away from any national agendas. These new works tend to apply eclectic approaches without having the need to highlight the issues prevalent in the current situations. The notion of Art for the sake of the society had been long exhausted and the current audience’s demands have since changed from the past. This paper traces the tendencies of the two short stories written by two contemporary writers who tried to draw away from fulfilling such ideologies. The research focuses on two short stories namely, Kuda Kepang by Fadzlishah Johanabas and Little Sweet by Ernie Yap. It will examine the ways in which these two writers have explored the supernatural elements in their works through the lens of magical realism. It is found that these two writers tend to communicate with their readers through their cultural backgrounds. It can be postulated that these explorations of their cultural experiences in their writings are to be purely creative and experimental. The experimentation with such mystical elements indicates that although there were no such attempts to project any ideologies, these two works proved that good literary texts can always be entertaining yet didactic.